Nanoclay and swift heavy ions induced piezoelectric and conducting nanochannel based polymeric membrane for fuel cell - Jana K.K.; Srivastava A.; Parkash O.; Avasthi D.K.; Rana D.; Shahi V.K.; Maiti P. (My University, 2025)
Through nanochannels are fabricated in poly(vinylidene fluoride-co-hexafluoro propylene) films by bombarding swift heavy ions (SHI) of energy 80 MeV and thereby creating latent tracks in the ion passage followed by chemical etching of the amorphous track. The dimension of the nanochannel is varied from 34 to 65 nm using different fluences and by dispersing organically modified nanoclay in polymer matrix. The nanochannels are grafted with polystyrene using the free radicals caused by SHI irradiation followed by their sulfonation. Nanoclay nucleates piezoelectric β-phase in copolymer whose extent gets enhanced after irradiation, grafting and sulfonation leading to a better material. The efficiency of functionalized nanochannel conduction is studied through dc conductivity of the bulk film in the semiconducting range against the insulating nature of the pristine copolymer. Current-voltage (I-V) characteristic of the membrane exhibits strong fluence dependency and shows superior conduction in functionalized nanohybrid. Proton conductivity of the functionalized nanohybrid is 6.2 × 10-2 S cm-1, while methanol permeability drastically reduces indicating higher values of the selective parameter of the developed membrane as compared to Nafion. Membrane electrode assembly studies of functionalized nanohybrid show 0.63 V as open circuit voltage leading to power density of 30.8 mW/cm2, considerably higher than the functionalized copolymer. © 2015 Elsevier B.V. All rights reserved.